Deliberate Learning in Health Care: The Effect of Importing Best Practices and Creative Problem Solving on Hospital Performance Improvement. (October 2014) - Nembhard, Ingrid M.; Cherian, Praseetha; Bradley, Elizabeth H.
This article examines the effect on quality improvement of two common but distinct approaches to organizational learning: importing best practices (an externally oriented approach rooted in learning by imitating others' best practices) and internal creative problem solving (an internally oriented approach rooted in learning by experimenting with self-generated solutions). We propose that independent and interaction effects of these approaches depend on where organizations are in their improvement journey − initial push or later phase. We examine this contingency in hospitals focused on improving treatment time for patients with heart attacks. Our results show that importing best practices helps hospitals achieve initial phase but not later phase improvement. Once hospitals enter the later phase of their efforts, however, significant improvement requires creative problem solving as well. Together, our results suggest that importing best practices delivers greater short-term improvement, but continued improvement depends on creative problem solving.